1984
DOI: 10.1901/jaba.1984.17-327
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Assessment and Treatment of Chronic Food Refusal in Handicapped Children

Abstract: In this study, we examined the eating behavior of four handicapped children, none of whom exhibited self-feeding skills. All children had a history of food refusal and were nutritionally at risk; one child received all nourishment by way of gastrostomy tube. Baseline data taken during mealtimes indicated that all children accepted very little food, expelled food frequently, and engaged in a number of disruptive behaviors. Treatments consisted of one or more of the following contingent events: social praise, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 16 publications
7
115
0
3
Order By: Relevance
“…Thus, in the present programme, once children 'acquire the taste' for the fruits and vegetables, these foods provide their own intrinsic rewards to supplement and, in time, perhaps entirely replace the programme's extrinsic rewards. The effectiveness of the present study's extrinsic rewards in increasing consumption and liking of fruit and vegetables is consistent with the findings of many other studies that have used rewards to alter food consumption and choice (Bernal, 1972;Hatcher, 1979;Siegel, 1982;Riordan et al, 1984;Handen et al, 1986;Stark et al, 1986;Baer et al, 1987;Hendy, 2002;.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, in the present programme, once children 'acquire the taste' for the fruits and vegetables, these foods provide their own intrinsic rewards to supplement and, in time, perhaps entirely replace the programme's extrinsic rewards. The effectiveness of the present study's extrinsic rewards in increasing consumption and liking of fruit and vegetables is consistent with the findings of many other studies that have used rewards to alter food consumption and choice (Bernal, 1972;Hatcher, 1979;Siegel, 1982;Riordan et al, 1984;Handen et al, 1986;Stark et al, 1986;Baer et al, 1987;Hendy, 2002;.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is also a large body of research testifying to the efficacy of rewards (eg see Dickinson, 1989;Cameron et al, 2001). A number of studies, for example, have employed them successfully to encourage food consumption among children with feeding difficulties (Bernal, 1972;Hatcher, 1979;Siegel, 1982;Riordan et al, 1984;Handen et al, 1986) and to increase children's healthy snack choices (Stark et al, 1986;Baer et al, 1987). This evidence indicates that, when used appropriately, rewards can be very effective at altering behaviour such as children's food consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, antecedent-based procedures were used to decrease the value of escape. These procedures included simultaneous presentation of preferred and non-Study Goals Procedures Results Riordan et al (1980) Increase variety and quantity of foods consumed DRA + demand fading Contingent access to preferred foods (without EE) resulted in an increase in bite acceptance of non-preferred foods, and demand fading resulted in an increase in the total volume of oral intake Riordan et al (1984) Increase variety of foods consumed DRA Contingent access to preferred foods and ignoring disruptive mealtime behavior (without EE) resulted in increased acceptance of non-preferred foods for the participants who exhibited food selectivity Cooper et al (1999) Increase variety and quantity of foods consumed DRA with/without EE (NRS)…”
Section: What Types Of Procedures Have Beenmentioning
confidence: 99%
“…In the studies on DRA included in this review, preferred foods or drinks were always used as positive reinforcers, either alone or in combination with social praise (Brown, Spencer, & Swift, 2002;Cooper et al, 1999;Levin & Carr, 2001;Riordan, Iwata, Wohl, & Finney, 1980;Riordan, Iwata, Finney, Wohl, & Stanley, 1984). Thus, the effectiveness of stimuli other than preferred foods or drink remains unclear.…”
Section: Differential (Positive) Reinforcement Of Alternative Behaviomentioning
confidence: 99%
“…DESCRIPTORS: descriptive assessment, feeding disorders, functional analysis, negative reinforcement A feeding disorder is identified when a child is unable or refuses to eat or drink suf-feeding problems or factors that maintain feeding problems. Rather, the vast majority of research on feeding problems has focused on treatments to increase acceptance and decrease problematic mealtime behavior (e.g., Ahearn, Kerwin, Eicher, Shantz, & Swearingin, 1996;Cooper et al, 1999;Hoch, Babbitt, Coe, Krell, & Hackbert, 1994;Kelley, Piazza, Fisher, & Oberdorff, 2003;Patel, Piazza, Kelly, Ochsner, & Santana, 2001;Patel, Piazza, Martinez, Volkert, & Santana, 2002;Piazza et al, in press;Riordan, Iwata, Finney, Wohl, & Stanley, 1984;Riordan, Iwata, Wohl, & Finney, 1980). These studies have shown that treatments based on operant consequences (e.g., escape extinction) are effective for increasing consumption in children with feeding problems (Ahearn et al; Cooper et al; Hoch et al; Patel et al, in press).…”
mentioning
confidence: 99%